2020
DOI: 10.3389/fphar.2019.01512
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Krüppel-Like Factor 4 Suppresses Migration and Invasion of Non-Small Cell Lung Cancer Through c-Jun-NH2-Terminal Kinase/Epithelial-Mesenchymal Transition Signaling Pathway

Abstract: Krüppel-like factor 4 (KLF4) is a transcription factor and plays a vital role in cancer initiation and development. However, the role of Krüppel-like factor 4 in the metastasis of non-small cell lung cancer (NSCLC) is not clear. Here, we demonstrated that the expression of Krüppel-like factor 4 was significantly decreased in human non-small cell lung cancer tissues compared with that in normal tissues using Western blot. We performed immunohistochemical staining and observed the decreased expression of Krüppel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 50 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…Noticeably, KLF4 KO impact on KLF2 expression is also dependent on the CFTR status ( Figure 3), and KLF2 has been shown to mediate EMT [46]. Consistently, KLF4 has been shown to prevent EMT in human corneal epithelia [47] as well as in some types of lung cancers [48]. In fact, in some contexts, it has been shown that KLF4 actively promotes mesenchymal-to-epithelial transition, i.e., MET [49].…”
Section: Discussionmentioning
confidence: 67%
“…Noticeably, KLF4 KO impact on KLF2 expression is also dependent on the CFTR status ( Figure 3), and KLF2 has been shown to mediate EMT [46]. Consistently, KLF4 has been shown to prevent EMT in human corneal epithelia [47] as well as in some types of lung cancers [48]. In fact, in some contexts, it has been shown that KLF4 actively promotes mesenchymal-to-epithelial transition, i.e., MET [49].…”
Section: Discussionmentioning
confidence: 67%
“…Fadous-Khalife et al reported that KLF4 expression is related to the clinicopathological characteristics of lung cancer patients and is a potential biomarker of lung cancer [10] , but its research has some shortcomings such as the small number of included tissue samples. Our preliminary basic research found that KLF4 can inhibit the metastasis of NSCLC [11] . In order to further study the expression of KLF4 in NSCLC and its clinicopathological correlation with NSCLC, this study intends to include surgical tissue samples from 155 patients with NSCLC, and draw conclusions by KLF4 immunohistochemical staining and statistical analysis.…”
Section: Introductionmentioning
confidence: 83%
“…KLF4 is an important suppressor of lung cancer [ 67 , 68 , 69 , 70 ]. It inhibits migration, invasion and metastasis of non-small cell lung cancer (NSCLC) cells by attenuating TGF-β1-induced EMT and inhibiting the c-Jun-NH 2 -terminal kinase signaling pathway [ 68 ]. However, as the Authors of the latter study acknowledge, the mechanistic explanation for the observed phenomena is lacking [ 68 ].…”
Section: Lung Cancermentioning
confidence: 99%
“…KLF4 is an important suppressor of lung cancer [67][68][69][70]. It inhibits migration, invasion and metastasis of non-small cell lung cancer (NSCLC) cells by attenuating TGF-β1-induced EMT and inhibiting the c-Jun-NH 2 -terminal kinase signaling pathway [68].…”
Section: Lung Cancermentioning
confidence: 99%